DESIGNING TRAINING SESSIONS FOR WORKING WITH INFORMATION THROUGH CREATIVE METHODS - Tokhirov Farruhbek Bakhtiyorovich (Bright Mind Publishing, 2025)
This article presents the methodology for designing and implementing training sessions aimed at developing information literacy competencies through creative approaches. The paper explores the effectiveness of creative methods-particularly brainstorming, clustering, concept mapping, and case studies-in cultivating participants’ skills in information search, analysis, synthesis, and evaluation.
Keywords: Creative approach, development of information competence, training design, methodology, professional development, interactive learning.